Antibacterial prophylaxis in neutropenic children with cancer - Barone, Angelica (PAGEPress Publications, 2011)
During the period of neutropenia induced by chemotherapy, patients have a high risk of infection. The use of antibiotic prophylaxis to reduce neutropenia-related complications in patients with cancer is still disputed. Recent meta-analysis and clinical trials demonstrated that antibiotic prophylaxis with quinolones reduces febrile episodes, bacterial infections and mortality in adult oncological patients with neutropenia induced by chemotherapy in acute leukaemia. In paediatric patients, the only randomized, double-blind, prospective study until now suggests that amoxicillin/clavulanate may represent an effective prophylactic treatment in reducing fever and infections in oncological children with neutropenia, with an efficacy that is statistically demonstrated only in patients with acute leukaemia. Considering the risk of resistances, antibiotic-prophylaxis should be used only in selected patients.